Preservation of the Indigenous Medicinal Knowledge Network of the Bonda Tribe - Kumari, Alka; Deb, Atanu; Prusty, Ajay Kumar; Suman, Swati; Rout, Dwity Sundar; Amar, Amritesh Kumar (Indian Journal of Extension Education, 2024)
For tribal people to preserve their historical legacy and advance environmentally friendly healthcare habits, traditional medicinal knowledge must be preserved. This is especially true for the Bonda tribe in the Malkangiriarea of Odisha. The Bonda tribe, who live in the Eastern Ghats, mostly depend on narrative Indigenous Medicinal Knowledge (IMK) shared among elders and traditional healers (Desaris). This study investigated the processes of knowledge transmission, the social networks that sustained the IMK system, and the preservation and ways adopted in Bonda Community. Data were gathered from multiple Bonda villages using purposive samplingtechnique during 2023-24 years. Qualitative methods and participatory research were used for data collection, and chord diagrams were used for visualization. The results showed a strong IMK network with important contributions from Desaris and strong community linkages.Thepreservation of sanctified groves and therapeutic herbsthrough conservation techniques, incorporating new information and preserving transmission secrecy were examples of adaptation tactics. This investigation promotedapproaches that encouraged safeguarding Indigenous Medicinal Knowledge (IMK) by highlighting the significance of Indigenous Knowledge Network (IKN) in maintaining traditional identities and social well-being.